2016
DOI: 10.1021/acs.jmedchem.6b01025
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bond-Containing Ajoene Analogues As Novel Quorum Sensing Inhibitors of Pseudomonas aeruginosa

Abstract: Since its discovery 22 years ago, the bacterial cell-to-cell communication system, termed quorum sensing (QS), has shown potential as antipathogenic target. Previous studies reported that ajoene from garlic inhibits QS in opportunistic human pathogen Pseudomonas aeruginosa. In this study, screening of an in-house compound library revealed two sulfur-containing compounds which possess structural resemblance with ajoene and inhibit QS in bioreporter assay. Following a quantitative structure-activity relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 66 publications
0
89
0
1
Order By: Relevance
“…Many studies have confirmed the synergistic effect of antibiotics and anti-QS agents ( Table 6). Ajoene, furanone c-30, and horseradish extract have been revealed to reduce the expression of virulence factors in Pseudomonas aeruginosa and make Pseudomonas aeruginosa easier to be cleared by tobramycin [107][108][109][110][111]. Another study has confirmed the synergistic effects of curcumin, gentamicin, and azithromycin on Pseudomonas aeruginosa; that is, the expressions of virulence genes were significantly downregulated by the combining use of curcumin together with gentamicin or azithromycin, and the therapeutic doses of gentamicin and azithromycin were minimized by curcumin supplementation [112].…”
Section: Combinations Of Anti-qs Agents and Antibioticsmentioning
confidence: 99%
“…Many studies have confirmed the synergistic effect of antibiotics and anti-QS agents ( Table 6). Ajoene, furanone c-30, and horseradish extract have been revealed to reduce the expression of virulence factors in Pseudomonas aeruginosa and make Pseudomonas aeruginosa easier to be cleared by tobramycin [107][108][109][110][111]. Another study has confirmed the synergistic effects of curcumin, gentamicin, and azithromycin on Pseudomonas aeruginosa; that is, the expressions of virulence genes were significantly downregulated by the combining use of curcumin together with gentamicin or azithromycin, and the therapeutic doses of gentamicin and azithromycin were minimized by curcumin supplementation [112].…”
Section: Combinations Of Anti-qs Agents and Antibioticsmentioning
confidence: 99%
“…A number of publications have identified natural compounds and their synthetic analogues that interfere with QS and that have been shown to reduce virulence factor expression in vitro or virulence in vivo [10][11][12][13][14][15][16][17]. Some natural foods have compounds with QS inhibitory activity, and such foods might offer a natural prophylaxis against chronic P. aeruginosa infections [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria were grown in Luria-Bertani (LB) broth (1% tryptone, 0.5% yeast extract, and 0.5% NaCl). Media used for biological assay was ABTGC (AB minimal medium supplemented with 0.2% glucose and 0.2% casamino acids) 62 . Bacterial strains used in this study are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%